MANAJEMEN PESERTA DIDIK DALAM MENGEMBANGKAN KEGIATAN EKSTRAKURIKULER DI MADRASAH ALIYAH SWASTA AINUL YAQIN KOTA JAMBI - Nurmiza Rahmatuddini; Sumirah Sumirah; Boby Yasman Purnama (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the management of students in developing extracurricular activities in private aliyah madrasah Ainul Yaqin, Jambi City and identify inhibiting factors in its implementation. This research is a qualitative research with a descriptive method, because it aims to obtain an in-depth picture of the process of managing students in extracurricular activities. The data collection techniques used include interviews, observations, and documentation involving the head of the madrasah, deputy head of the madrasah, extracurricular coaches, and students. The results of the study show that the management of participants in developing extracurricular activities is carried out through the planning, organizing, implementation, and evaluation stages that are adjusted to the conditions of the madrasah. Although extracurricular activities have been running, in their implementation there are still several obstacles, especially limited funds and supporting facilities and infrastructure, which have an impact on the smooth and consistent implementation of several extracurricular activities. However, the madrasah still strives to maintain the sustainability of extracurricular activities through support from the foundation, cooperation with students' parents, and utilizing the available facilities so that extracurricular activities continue to run and function as a means of developing students' interests and talents.